Alterações de expressão gênica na linhagem de glioblastoma humano U87 após exposição ao MeHg e HgCl2 - GOMES, Bruna Puty Silva (Universidade Federal do Pará, 2017)
The organic and inorganic forms of mercury have been pointed as important contaminants in several world regions due to its toxicological characteristics. Various studies have reported that the intoxication by methylmercury (MeHg) and mercury chloride (HgCl2) can lead to central nervous system impairment. It is generally agreed that glial cells are important for the mechanisms responsible for cellular protection against the damages caused by the mercury. However, little is known about the influence of the mercury in the cells genome. Hence, in the present study we did a complete mapping of the humam glial cells genetic network after mercury exposition with the aim to indentify the possible genetic alterations that occurred via the organic and inorganic forms of mercury. Our results demonstrated that U87 lineage cells are more sensitive to MeHg exposition when compared with HgCl2 exposition. Using an analysis of the concentration curves the LC50 was obtained from 28.8μM and 10,68μM after 4h and 24h exposition to MeHg and a LC50 of 92.25μM and 62.75μM after the same time periods exposition to HgCl2. Regarding the genic pool, our results have shown that both metal forms led to alterations in the genic dosage where the MeHg exposition was highly influenced by the concentration and time, whereas the HgCl2 exposition seemed have been strongly influenced by the exposition time. In total there were 205 indentified genes with a lower genic dosage and 188 genes with elevated expression, (Fold change > 5) after 4h exposition and 5μM of MeHg, and 204 down-regulated genes; and 180 up-regulated genes after HgCl2 exposition in the same concentration. The analysis after 24h exposition showed 90 down-regulated genes and 3 up-regulated genes after 1μM of MeHg; 116 genes were down-regulated and 66 genes were up-regulated after a 10μM exposition of MeHg. As for the HgCl2, there were 98 down-regulated genes and 73 up-regulated genes for the groups exposed to 5μM of HgCl2; 326 down-regulated genes and 66 up-regulated genes for the groups exposed to 62,75μM of HgCl2. Our dataset suggests that both mercurial forms are able to alter the cell genetic expression profile thus interfering in important signaling paths prone to gives rise to biochemical impairments and glial cells phenotypes.